SEJARAH ETNIS TIONGHOA DI TANJUNGPINANG - Ade Prasetyo; Isjoni Isjoni; Bedriati Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Tionghoa-Indonesia ethnic is one of the ethnic groups in indonesia whose ancentral origins come from China. Tanjung Pinang is a city dominated by Tionghoa ethnic with a percentage of 58.86%. Tanjungpinang is inhabited by diverse population of ethnic groups, hence since the beginning of their arrival, the chinese ethnic must be interact with these different groups. Therefore Tionghoa ethnic develops into a separate society in the midst of complex social, cultural, economic and political life in Tanjungpinang. The purpose of this study : 1) to discover the beginning of the arrival of chinese ethnic in Tanjungpinang; 2) to learn the adaptation of Tionghoa ethnic in interacting with community in Tanjungpinang, 3) to ensure the development of the chinese ethnic community in Tanjungpinang during the new era period between 1965-1998; 4) to determine the impact of the arrival of the Tionghoa ethnic in Tanjungpinang within the social, economic and culture fields. This research uses historical method. Historical method is a method that focuses on past research implement by gathering previous research sources that are used as a reference in writing history. The arrival of Tionghoa ethnic in Tanjungpinang began when Malay and Bugis noblemen brought large numbers of Tionghoa people from Malacca to become uncaria gambir plantation workers. In conclusion, the factor that cause the entry of Tionghoa ethnic in Tanjungpinang is because there are certain interests related to the exploitation of natural resources, which is to be employed as gambir plantation workers. The existence of Tionghoa ethnic in tanjungpinang had an impact on society in terms of Both economy and culture. In the economic field, the Tionghoa ethnic are able to increase economic growth in Tanjungpinang, this is evidenced by the large number of private companies established by them. Moreover, in culture field the existence of Tionghoa ethnic could also gives the diversity of traditions such as Chinese New Year celebrations, Cap Go Meh, Chinese New Year bazaar, dragon boat show as well as lion dance performance.Key Words: Tionghoa Ethnic,Tanjungpinang